Development of a Mental Health Objective Structured Clinical Examination (OSCE): A Pilot Study. (August 2019) - Stockmann, Cherrill; Diaz, Desiree A.; Murphy, Debra; Dever, Kimberly; Marchini, Michelle; Huffman-Frazee, Jodi; Anderson, Mindi
Background. An Objective Structured Clinical Examination (OSCE ) is an effective means for clinical evaluation related toclinical competence . Historically, clinical assessment is based on direct observation which can be rooted in subjectivity. Evidence is minimal regarding psychometric properties of anOSCE in undergraduate mental healthnursing education, although established as a valid measure ofclinical competence . Method. A pilot study was conducted with a convenience sample of 13 sixth semester nursing students to evaluate thevalidity andreliability of anOSCE framework designed to assess undergraduate mental health nursing students'clinical competence . The research questions asked: What are the psychometric properties of a mental healthOSCE developed for undergraduatenursing education ? How do students perceive theOSCE ? Results. Preliminaryvalidity andreliability measures were established, including content and criterion validities and inter-raterreliability . Students perceived theOSCE as both a beneficial and challenging learning experience. Conclusion. TheOSCE was initially established as a valid, reliable tool for the assessment ofclinical competence in undergraduate mental healthnursing education . This evaluation method may be used to objectively assess mental health nursing knowledge, skills, and attitudes in conjunction with existing clinical assessment methods to provide a valid, reliable measure ofclinical competence . More testing is needed.